Topory kamienne i siekiera krzemienna z okolic Giecza (pow. średzki wielkopolski, woj. wielkopolskie) w kontekście osadnictwa neolitycznego - Indycka, Elżbieta (Folia Praehistorica Posnaniensia, 2015)
The aim of the article is to discuss two previously unpublished Neolithic stone axes and a flint one, found in the vicinity of the Archaeological Reserve in Giecz. The artefacts have been discussed in the context of the Neolithic settlement from the area of their discovery.